BENEFITS AND CHALLENGES OF IMPLEMENTING BLENDED LEARNING: A LITERATURE REVIEW - Mesakh Tamu Ama (Adisam Publisher, 2026)
This study aims to explore the key benefits of blended learning in educational institutions and the challenges educators/teachers and students face in the implementation of blended learning. With the use of a systematic literature review, 25 research papers were synthesized. To ensure a rigorous selection of relevant research studies on the topic while remaining flexible to include diverse views, this study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework across multiple databases, including Google Scholar, Scopus, and Mendeley. The research revealed that blended learning benefits students in a few different ways, e.g., increased autonomy, greater flexibility, inclusivity, support for diverse learning styles, and development of transferrable skills. There are also some challenges that both students and teachers still have to face. Internally, students are faced with distractions, especially from social media, and feelings of isolation, while teachers deal with resistance to change, low self-confidence, and increased workload. Externally, there is still a technological divide between rural and urban areas, a lack of teachers’ involvement in the decision-making process, and a lack of clear policies and strategic direction within educational institutions.